Use of Balint Groups (BGs) to Support Wellbeing Amongst Medical Students in a Public Health Institution - Lay Ling Tan; Karen Koh (BJPsych Open)
Aims: BG is named after its founder, Michael Balint, a trained therapist. BGs are reflective practice groups and have been shown to help with critical reflection, self-discovery and deep connection to others. It can enhance empathic understanding of the doctor-patient therapeutic relationship and has been used to facilitate reflections amongst doctors and other healthcare professionals. Its application in medical students have not been widely studied.